2016
DOI: 10.1021/jacs.6b07259
|View full text |Cite
|
Sign up to set email alerts
|

Helical Conformation in the CA-SP1 Junction of the Immature HIV-1 Lattice Determined from Solid-State NMR of Virus-like Particles

Abstract: Maturation of HIV-1 requires disassembly of the Gag polyprotein lattice, which lines the viral membrane in the immature state, and subsequent assembly of the mature capsid protein lattice, which encloses viral RNA in the mature state. Metastability of the immature lattice has been proposed to depend on the existence of a structurally ordered, α-helical segment spanning the junction between capsid (CA) and spacer peptide 1 (SP1) subunits of Gag, a segment that is dynamically disordered in the mature capsid latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…A potent maturation inhibitor, Bevirimat (BVM), blocks CA-SP1 cleavage and prevents formation of the mature conical capsid [19][20][21][22] . Recent structural and mutational studies have indicated that the junction between CA and SP1 could act as a molecular switch to regulate immature Gag assmebly and protease cleavage [23][24][25][26] . Structural analyses of the Gag lattice in mutant viruses that have impaired cleavage of Gag at specific sites suggest that processing is ordered and that the RNA/protein complex (RNP) may maintain a link with the remaining Gag lattice after cleavage 27 .…”
Section: Introductionmentioning
confidence: 99%
“…A potent maturation inhibitor, Bevirimat (BVM), blocks CA-SP1 cleavage and prevents formation of the mature conical capsid [19][20][21][22] . Recent structural and mutational studies have indicated that the junction between CA and SP1 could act as a molecular switch to regulate immature Gag assmebly and protease cleavage [23][24][25][26] . Structural analyses of the Gag lattice in mutant viruses that have impaired cleavage of Gag at specific sites suggest that processing is ordered and that the RNA/protein complex (RNP) may maintain a link with the remaining Gag lattice after cleavage 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state NMR is ideal for studies of large protein complexes and membrane proteins because it is not reliant on long range order, solubility, or rapid tumbling [5]. In the past decade, solid-state NMR has been used to study a variety of biological systems such as HIV-1 capsid protein assemblies [6][7][8][9][10][11], 300 kDa GB1-antibody complexes [12,13], and membrane-bound influenza M2 proton channels [14][15][16]. Such NMR studies have also provided measurements of protein dynamics [17][18][19] and identification of disordered regions [20][21][22][23][24].Research in recent years on intrinsically disordered proteins (IDPs) and intrinsically disordered regions (IDRs) has highlighted the importance of disordered regions in the function of many proteins.…”
mentioning
confidence: 99%
“…In 2016, compelling evidence for the predicted 6-helix bundle structure of the junction helices was provided by electron cryotomography and subtomogram averaging of ΔMA-Gag, non-enveloped virus-like particles (VLPs) 16 , X-ray crystallography of a Gag construct comprised of the C-terminal domain (CTD) of CA and SP1 17 , and solid-state NMR spectroscopy of ΔMA-Gag VLPs 18 . The cryoEM and X-ray structures revealed that the protease cleavage sites are sequestered on the interior of the 6-helix bundle.…”
mentioning
confidence: 99%